MLOPs Foundations : Chapter 2 Walkthrough of Practical MLOps - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn the foundations of MLOPs Topics include: * Linux and Bash * AWS Cloud9 and AWS Cloud Shell and other Cloud Topics * The intuition behind MLOps techniques: optimization, gradient descent and data science.